The Vina Cirebon Case: Social Media as a Means of Seeking Justice (Oratio Directa, 2024)
The adage 'no viral, no justice' has gained prominence in Indonesian legal discourse. The murder case of Vina Cirebon received renewed legal attention after becoming viral on social media. Netizens collectively searched for online and field data, prepared investigative accounts, and distributed them through social media. Some acted as citizen journalists whose findings contributed information relevant to the legal process. Social movement theory explains that collective action outside established institutions can influence public institutions. In this case, netizens used social media as a means of social and legal resistance in seeking justice.
Keywords: Social media; Citizen journalism; Social movements; Legal justice; Collective action